Burden of Antimicrobial Resistance in Adult Hospitalized Patients With Cancer: A Multicenter Analysis - Vikas Gupta; Michael J. Satlin; Kalvin Yu; Yehoda M. Martei; Lillian Sung; Lars F. Westblade; Scott C. Howard; ChinEn Ai; Diane C. Flayhart (Cancer Medicine)
ABSTRACT Background Infections are a leading cause of death in patients with cancer, but the proportion and rate of antimicrobial resistance (AMR) in hospitalized patients with cancer are not well understood. Methods This retrospective, cross‐sectional evaluation of AMR assessed hospitalized adult patients in 168 United States (US) healthcare facilities between April 2018 and December 2022. Nonduplicate, noncontaminant Gram‐negative and Gram‐positive bacteria recovered from various samples (blood, respiratory, urine, etc.) were used to assess the rate of AMR pathogens per 1000 admissions and the proportion of AMR among bacterial isolates in patients with and without cancer. Findings Among 4,612,620 admissions, 6.4% (297,500) were of patients with cancer and 93.6% (4,315,120) were of patients without cancer. AMR pathogen rates were higher in cancer patients than patients without cancer for most pathogen groups, including vancomycin‐resistant enterococci with incidence rate ratio (IRR), 1.95 (95% confidence interval [CI], 1.84, 2.07), extended‐spectrum beta‐lactamase (ESBL) producers (IRR, 1.48 [95% CI, 1.43, 1.53]), carbapenem‐nonsusceptible Enterobacterales (IRR, 1.46 [95% CI, 1.32, 1.61]), and multidrug‐resistant Pseudomonas aeruginosa (IRR, 1.31 [95% CI, 1.18, 1.45]). The percentage of nonsusceptible isolates in most pathogen groups was lower in patients with versus without cancer except for ESBL producers among Enterobacterales (odds ratio (OR), 1.11 [95% CI, 1.07, 1.15]) and vancomycin resistance among enterococci (OR, 1.22 [95% CI, 1.14, 1.30]), which were higher in cancer patients. Conclusion AMR rates for certain key pathogens were 1.5–2 times greater in hospitalized cancer patients compared to hospitalized noncancer patients. The increased AMR rate in cancer patients highlights the need for enhanced infection prevention and diagnostic stewardship efforts.